The Length of the Staphylococcus aureus Protein A Polymorphic Region Regulates Inflammation: Impact on Acute and Chronic Infection - Garofalo, Ailin Natalia (2012)
Staphylococcus aureus protein A (SpA) plays a critical role in the induction of inflammation. This study was aimed to determine whether the number of short sequence repeats (SSRs) present in the polymorphic region modulates the inflammatory response induced by SpA. We demonstrated that there is a dose-response effect in the activation of IFN-â signaling in airway epithelial and immune cells depending upon the number of SSRs which leads to differences in neutrophil recruitment. We also determined that a significant proportion of isolates from patients with chronic infections such as osteomyelitis and cystic fibrosis carry fewer SSRs than isolates from patients with acute infections or healthy carriers and there was an inverse correlation between the number of SSRs and the length of disease. Given the importance of IFN signaling in eradication of S. aureus, loss of SSRs may represent an advantageous mechanism to adapt to and persist in the host.